The evolution of programs and teaching methods for tourism and leisure ecnonomics: The University of Physical Education in Krakow - Szczechowicz, Bartosz; Stelmach, Paweł (Turyzm/Tourism, 2017)
The aim of the article is to answer the question: what can non-economic universities do to improve their curricula for economic modules and methods of implementation? Literature review, participant observation and descriptive statistics were used based on an original set of 430 projects from the ‘Marketing of tourism and leisure services’ course for the academic years 2014/15, 2015/16 and 2016/17. Adopting a student orientation as a long-term partner in the information exchange process, in line with the concept of relationship marketing, contributes to the intensification of the didactic process aimed at broadening knowledge of economic reality.